Estimation of arsenic in nail using silver diethyldithiocarbamate method (Bangladesh Journal of Pharmacology, 2015)
Spectrophotometric method of arsenic estimation in nails has four steps: a) washing of nails, b) digestion of nails, c) arsenic generation, and finally d) reading absorbance using spectrophotometer. Although the method is a cheapest one, widely used and effective, it is time consuming, laborious and need caution while using four acids.  Video ClipsNail wash:                 3.2 minDigestion of nail:        7.0 minArsine generation:     10.0 minReading absorbance:   1.2 min